Penguatan Literasi Membaca melalui Model LOK-R pada Siswa SDIT Al Hambra Pesawaran - Muhammad Singgih; Atika Nur Hidayati; Nita Septiani (Al Mufid, 2024)
Literacy is one of the main foundations that must be taught at the elementary school level. If the literacy foundation is strong since elementary school, students will adapt more quickly to learning. The lack of literacy culture in today's children and youth environment needs to be recognized. This encouraged the team to carry out PkM with the title PkM "Strengthening Reading Literacy through the LOK-R Model for SDIT Al Hambra Pesawaran Students". This activity was carried out as an effort to strengthen the literacy of elementary school age children through the LOK-R model at the Al Hambra Pesawaran Integrated Islamic Elementary School. This is motivated by the fact that there is still a lack of students' reading literacy skills so it is necessary to implement a model that helps students become more interested in reading. This community service provides participants (students) with experience on how to use the LOK-R model in increasing the reading literacy of students at the Al Hambra Pesawaran Integrated Islamic Elementary School. Therefore, the Literacy Orientation Collaboration Reflection (LOK-R) learning model is suitable for learning in elementary schools